Standardizing Life Cycle Organization: A Synergetic Quality Management Approach - Prokopovych I. V.; Kokhanov A. B.; Khamitov V. M.; Tikhenko V. M.; Predrag Dašić (Журнал інженерних наук)
Standardization is essential for innovation (on the impacts on design, manufacturing, and operation processes) and its dissemination, both within a country and internationally. A phenomenological information model has been developed for the system of standards, which will be used as an information base for integrated quality management systems, environmental safety, and energy saving depending on the type of products, requirements of technical regulations, and conformity assessment procedures. Phase portraits of the life cycle system of complex products were constructed, and a general expression for the Lyapunov exponents characterizing the overall behavior of the dynamic system in phase space was obtained. The presence of particular areas to which, regardless of the initial conditions, all phase trajectories rapidly evolve has been established. The critical conditions for the control parameters were found. A diagram was constructed that determines the stability of the system states of the life cycle of complex products. It was found that the processes of the life cycle of complex products are carried out in two stages: in the first, there is a rapid evolution of components and parameters of technical and software tools, as well as energetic elements of functional subsystems, which is reflected in a specific attractive section of phase portraits, in the second, further slow development along it.